Catalyst-Controlled Strategies to Override the Bond Dissociation Energy-Driven Selectivity of Benzylic C(sp3)–H Insertions - Brunard, Erwan; Boquet, Vincent; Bissonnier, Théo; Saget, Tanguy; Carrizo, E. Daiann Sosa; Sircoglou, Marie; Dauban, Philippe (Synlett, 2024)
Catalytic C(sp3)–H insertion reactions of arylalkanes generally proceed at the benzylic position as a consequence of the lower bond dissociation energy (BDE) of the corresponding C–H bond. This account gives a brief overview of recent studies aimed at designing catalyst-controlled amination reactions to go beyond this BDE-driven selectivity. They permit the selective conversion of neutral C–H bonds with a BDE greater than 95 kcal mol–1 for the formation of alkylamines.1 Introduction2 Catalyst-Controlled Site-Selective C–H Insertion Reactions3 Catalyst-Controlled Intermolecular Amination of Nonactivated C–H Bonds of Arylalkanes4 Conclusion
Keywords: rhodium catalysis; nitrene; amination; C–H functionalization; regioselectivity; C–N bond formation